(untitled) - Robertson, Gordon L. (Boca Raton, FL, 2006)
Originally published in 1993, Food Packaging: Principles and Practice went on to become a best-selling textbook and industry standard. The second edition continues this tradition, with an integrated approach toward the study of packaging technology that covers chemistry, microbiology, and engineering, but with significant additions. Five brand new chapters along with numerous diagrams have been incorporated to explain recent developments in processes and equipment. The author has updated all of the references and added a chapter explaining new and active packaging technologies. This second edition adheres to the essential format that made the first edition so informative and accessible.
Keywords: Food,Food science and technology (Taylor & Francis),Thực phẩm; Packaging,Đóng gói